PERANCANGAN SISTEM PELAYANAN DESA MENGGUNAKAN RFID BERBASIS WEB - Aditya Fatwa Komara; Ii Sopiandi (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
This research aims to propose a web-based RFID (Radio Frequency Identification) system for enhancing village service management. In many rural areas, managing and monitoring various services provided to the villagers often face inefficiencies and delays due to manual processes and paperwork. The integration of RFID technology into the service delivery process can significantly improve the efficiency, transparency, and accountability of village services. The study begins with an analysis of the current service management system in the target village, identifying key challenges and bottlenecks. Through a comprehensive literature review, the benefits of RFID technology in diverse sectors are explored, highlighting its potential applicability in the context of village services. The proposed system encompasses the deployment of RFID tags to uniquely identify villagers and various village services such as healthcare, education, welfare distribution, and administrative tasks. A web-based platform will be developed to facilitate real-time data collection, analysis, and reporting. Additionally, the system will enable efficient tracking of service requests, delivery status, and resource allocation.